Rote Learning Methods on Islamic Education Subject in Relation with students' Learning Motivation - Ilham Faisal Abduh; Aditya Taqwa (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2022)
The purpose of this study was to find out students' responses to the use of Rote Learning methods in Islamic Religious Education (PAI) lessons; students' learning motivation; and the relationship of students' responses to the use of Rote Learning methods in PAI lessons with their learning motivation. In this study, it used quantitative approaches with the conventional association method, the types of gained data are quantitative and qualitative data. The data sources in this study used primary and secondary data sources, and the technique of collecting data used questionnaires, observations, literature studies, and interviews. Based on the results of the study, it was gained that students' responses to the use of the Rote Learning method got an average score of 3.23 with neutral categories. Students' learning motivation obtained a score of 3.56, with a high category. While the relationship between students' responses to the use of the Rote Learning method and their learning motivation obtained a correlation value of 0.78 with high qualifications. The results of the hypothesis test showed t-count 8.30> ttabel 1.676. The conclusion of this study was obtained that the use of the Rote Learning method in the learning of Islamic religious education has a significant influence. Tujuan dari penelitian ini adalah untuk mengetahui tanggapan siswa terhadap penggunaan metode Rote Learning pada pelajaran PAI; motivasi belajar siswa; dan hubungan tanggapan siswa terhadap penggunaan metode Rote Learning pada pelajaran PAI dengan motivasi belajar siswa. Dalam penelitian menggunakan pendekatan Kuantitatif dengan metode Assosiatif correlasional maka jenis data yang dihasilkan yaitu data kuantitatif dan kualitatif. Sumber data dalam penelitian ini menggunakan sumber data primer dan sumber data sekunder, dan Teknik penggumpulan data menggunakan angket, observasi, studi kepustakaan, dan wawancara. Berdasarkan hasil penelitian diketahui bahwa tanggapan siswa terhadap penggunaan metode Rote Learning memperoleh nilai rata-rata 3,23 dengan kategori netral. Motivasi belajar siswa memperoleh nilai 3,56, dengan kategori tinggi. Sedangkan hubungan antara tanggapan siswa terhadap penggunaan metode Rote Learning dengan motivasi belajar siswa diperoleh nilai korelasi sebesar 0,78 dengan kualifikasi tinggi. Hasil pengujian hipotesis menujukan thitung 8,30> ttabel 1,676. Kesimpulan dari penelitian ini diperoleh bahwa penggunaan metode Rote Learning pada pembelajaran Pendidikan agama Islam terdapat pengaruh yang signifikan.